PENGARUH EKSTENSIFIKASI PAJAK, INTENSIFIKASI PAJAK, KENAIKAN PTKP, DAN TAX HOLIDAY TERHADAP PENERIMAAN PAJAK ORANG PRIBADI DI JAKARTA BARAT - Ngadiman, Ngadiman; Felicia, Felicia (Jurnal Akuntansi, 2017)
The purpose of research is to determine the influence of tax extensification, tax intensification, non-taxable income increases, and tax holiday to individual tax income. This research was conducted to 100 individual taxpayers respondents in Jakarta Barat. This research uses multiple linear regression models to test the hypothesis. The result of this research shows that tax extensification, tax intensification and non-taxable income increases have significant influence to individual tax income. While tax holiday has no significant influence to individual tax income.